Adoption of recommended practices for cultivation of cardamom (Elettaria cardamomum Maton) in the Hill Zone of Karnataka, India - VENKATAPPA, D RAGHUPATHI, R (Journal of Spices and Aromatic Crops, 1998)
A study was conducted in the Hill Zone of Karnataka, India, to find out the relationship of selected independent variables with dependent variables on adoption of improved practices for cultivation of M-1 variety of cardamom (Elettaria cardamomum). The study indicated that experience had a positive significant relationship with adoption of improved practices' and education and land holding had no significant relationship with the same.